Testing the stability of self-control: identifying unique developmental patterns and associated risk factors - Ray, James V. (Criminal justice and behavior, 2013)
Gottfredson and Hirschi suggest that individuals? levels of self-control remain stable over the life course; however, the empirical status of this proposition remains equivocal. Most tests of the stability hypothesis have employed aggregate assessment methods (e.g., mean-level and correlational analyses) that overlook unique developmental patterns, although some have identified unique developmental patterns in self-control. The current study assesses the stability of self-control across 4 years using both traditional analytic methods and methods that account for the existence of unique developmental patterns (i.e., semiparametric group-based trajectory modeling) and exploring risk factors that differentiate these patterns. The results suggest six unique developmental patterns of self-control: two with high stable trajectories and four that evinced lower, less stable trajectories of self-control. The findings indicate that lower, less stable patterns of development are associated with more delinquent peer association, higher rates of parental criminality, fewer school bonds, and weaker maternal attachment.